Kelori: Development of Moringa Leaves Based on Nori Products as a Solution to Increase Immune System - Ika Wisudawaty; Hasbi Hasbi; Wulan Purnamasari; Nurhalim Nurhalim; Uqbah Al Ansyari (PT. Global Research Collaboration, 2025)
Indonesia is one of the largest seaweed-producing countries in the world; however, the limited availability of Porphyra species hinders local nori production. The innovation of developing nori based on moringa leaves (Moringa oleifera) presents a promising alternative, considering moringa's high nutritional content, including protein, fiber, vitamins, minerals, and antioxidants that contribute to immune system enhancement. This activity represents a novel innovation in the development of functional food products by utilizing fresh moringa leaves as the main ingredient. The process begins with drying the moringa leaves using a low-temperature dehydrator to preserve their nutritional value. Next, the dried leaves are ground into a fine powder using a high-speed blender. This powder is then mixed with tapioca flour, egg white, and a pinch of salt using a horizontal dough mixer until a homogeneous mixture is formed. The mixture is flattened using a manual stainless steel nori sheet press and then dried again in a low-temperature air-circulating oven to produce thin, dry moringa nori sheets. Through this process, a product that has never been developed before—moringa-based nori—is created, characterized by a crispy texture, natural savory taste, and high nutritional value. This activity not only introduces a new method of moringa leaf processing but also opens opportunities for innovation using simple tools that can be replicated by local communities.